2017
DOI: 10.1136/bmj.i6865
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone treatment among pregnant women with subclinical hypothyroidism: US national assessment

Abstract: Objective To estimate the effectiveness and safety of thyroid hormone treatment among pregnant women with subclinical hypothyroidism.Design Retrospective cohort study.Setting Large US administrative database between 1 January 2010 and 31 December 2014.Participants 5405 pregnant women with subclinical hypothyroidism, defined as untreated thyroid stimulating hormone (TSH) concentration 2.5-10 mIU/L.Exposure Thyroid hormone therapy.Main outcome measure Pregnancy loss and other pre-specified maternal and fetal pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
170
1
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 25 publications
3
170
1
8
Order By: Relevance
“…This emphasizes the importance of screening all the mothers for hypothyroidism. 8 Effects of maternal hypothyroidism on fetal brain development are not well defined, several recent reports indicate that IQ is modestly affected (24-26). These studies have increased the concern that even mild hypothyroidism can interfere with normal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes the importance of screening all the mothers for hypothyroidism. 8 Effects of maternal hypothyroidism on fetal brain development are not well defined, several recent reports indicate that IQ is modestly affected (24-26). These studies have increased the concern that even mild hypothyroidism can interfere with normal brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent national survey in USA showed that thyroid hormone treatment was associated with decreased risk of pregnancy loss in women with subclinical hypothyroidism, but increased risk of other pregnancy related adverse outcomes such as preterm delivery, gestational diabetes or preeclampsia (11). All these data highlight the need of selective indications of therapy, based on sensible treatment threshold for women who have mildly increased TSH without other risk factors.…”
Section: Against Treating Subclinical Thyroid Dysfunctionmentioning
confidence: 99%
“…At present, much effort is being invested in order to reduce their impact on families and health services. In this regard, the recent results of levothyroxine use in reducing pregnancy loss and preterm delivery are certainly promising (11,76). However, it is important to highlight that all the interventions with levothyroxine (LT4) replacement performed to date did not include any other preventive or therapeutic approach: data are lacking regarding the effectiveness of LT4 in combination with aspirin for recurrent miscarriages or progesterone and/or pessary for preterm delivery; and these approaches should be evaluated through further studies.…”
Section: In Favour Of Treating Subclinical Thyroid Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…But associated with increased risk of preterm delivery, PIH and GDM. [24] But it was a retrospective observational study and use of administrative claims like potential for misclassification of treatment and confounders, lack of clinical details, selection biases related to health plan enrolment, diagnostic testing and treatment choice. Women with treated hypothyroid disease had an increased risk for PIH(4.3% vs 2.6%,p=0.03) compared to women without thyroid disease.…”
Section: Section: Obstetrics and Gynaecologymentioning
confidence: 99%